Peranan Modal Sosial Dalam Kegiatan Ekonomi - Chalid, Pheni (Signifikan: Jurnal Ilmu Ekonomi, 2012)
Trust in business is a fundamental element within capital and business success. Businesses need social interaction and networking. Hierarchical mechanism in the corporation, on the one hand aims to streamline the corporate performance targets in the pursuit of profit, but on the other hand there is the critical issue of how the relationship between the shareholders or the investors in monitoring the performance and behavior management in running the company. The problems is simply to look for answers from the existence of a contract containing agreements and management job descriptions, so that the irregularities that occurred outside the context of the contract will be consequential sanctions. The problem is, if then the existence of the contract will streamline the monitoring of behavior and performance management, which all it really comes down to mutual trust relationship, between management and shareholders.DOI: 10.15408/sjie.v1i1.2594